Utilization Instagram as an Communication Marketing Media - Asrul A; M Alfandy I; Aufa Fauziah S (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study is to analyze the use of Instagram as a communication marketing medium in utilizing the new internet media as an alternative to approach potential consumers. This study used qualitative research methods. The results of this study are the use of Instagram social media in expanding and improving the marketing communication function. Because the presence of the internet in marketing communications can help business people or marketers in carrying out marketing communications, because marketers must have a strategy to be able to take advantage of Instagram social media as a marketing medium in order to achieve their goals and target market. This research was conducted to determine the benefits of Instagram as a communication marketing medium in approaching consumers and achieving the desired target market